Hepatocellular Carcinoma: Systematic Review of Relevant Biomarkers and the Impact on Liver Resections - Bocșe, Horea; Ciocan, Andra; Zaharie, Florin V.; Ciocan, Răzvan A.; Al Hajjar, Nadim (International Journal of Innovative Research in Medical Science, 2022)
Background: Hepatocellular carcinoma (HCC) is the primary cancer of the liver representing the 6th cause of cancer worldwide and the 3rd in terms of deaths per year. Recent advances have offered new treatment options for this disease. New links between biomarkers and patients’ prognosis show a great potential for a more precise and targeted therapy. Method: A systematic review was performed following the guidelines outlined by The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Original articles published in the online database, Pubmed (Medline), Embase and Cochrane from January 2017 to February 2022 were screened after using specific keywords. Results: A total of 1300 studies was obtained by searching through online databases. Following the exclusion criteria, we included 18 studies in the systematic review. Conclusions: Biological markers are playing an important role for the prognosis of HCC. Alfa-fetoprotein (AFP) is still a valid biomarker, that can help stratify the risk for patients with HCC. Meanwhile, the current advancements in the field of miRNAs open new opportunities to analyse the role of miRNAs in HCC. Studies conducted on targeted therapies should also take into consideration the levels of these biomarkers, statistically linked with the prognosis of patients after liver resections.